PENGARUH PEMBERIAN INSULIN SECARA LOKAL PADA DAERAH FRAKTUR TERHADAP PENYEMBUHAN FRAKTUR PADA TIKUS PUTIH (RATTUS NOVERGICUS - , MUHAMMAD PANDU NUGRAHA; , Dr. Rahadyan Magetsari, Sp. OT., Ph.D., FICS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background Insulin has anabolic effects on fracture healing. Administration of local insulin delivery to the fracture site influences osteoblast proliferation and accelerates callus formation . Methods This study were to determine the effect of local intermediate-acting insulin delivery to the fracture site on bone healing that is assessed radiologically and histologically, and determine the occurence of any systemic effects. Ten units of intermediate acting insulin (Humulin N) were given locally to the fracture site of the Rattus Novergicus femoral shaft that has been fractured (n = 10) and the control group that were given Normal saline 0.9% (n = 10). Terminations were performed at week 4 and evaluations were done radiologically, histologically, and by determining osteoblasts count. Measurement of blood glucose and body weight were done to evaluate the systemic effect. Results and Discussion Examination of blood glucose and animal body weight showed that were no significant differences between intervention dan control group (p <0.05), indicating that there were no systemic effects in the experimental animals. Evaluation of radiological scoring (p = 0.013), histological scoring (p = 0.01) and osteoblasts count (p = 0.00) showed that there were significant differences compared to the control group (p <0.05). This study indicate that local intermediate-acting insulin delivery to the fracture site give better fracture healing in experimental animals without systemic effect.